Application of lyophilized purple-fleshed sweet potato powder as a multifunctional ingredient in Greek yogurt - Paulo Cezar da Cunha Júnior; Mariá Toledo de Carvalho Silva; Maria Ivone Martins Jacintho Barbosa; Elisa Helena da Rocha Ferreira (Ciência Rural, 2023)
ABSTRACT: Purple-fleshed sweet potato is a tuber rich in anthocyanins, which are phenolic pigments that confer color and present bioactive capacity. Moreover, its incorporation into dairy products can bring technological and functional benefits. Thus, this article evaluated the impact of the addition of lyophilized purple-fleshed sweet potato powder- LP (0% - Control, 2%, and 4%) on the physical, chemical, and technological characteristics of Greek yogurt. LP showed in vitro antioxidant and bioactive capacity by DPPH (20.64 ± 1.61 μmol TE g-1), FRAP (112.93 ± 4.38 μmol TE g-1), total phenolic content (103.66 ± 3.35 mg GAE g-1), and total anthocyanin content (51.10 ± 1.87 mg cyanidin 3-glucoside 100 g-1). Additionally, the assays demonstrated that the LP has 16.82 ± 0.63% of resistant starch. The fortification of Greek yogurt with LP reduced the syneresis, indicating that LP increased the water retention capacity. LP also inhibited the post-acidification process, increasing apparent viscosity, hardness, and gumminess, and promoting a stable pink coloration throughout the storage (P < 0.05). At the 4% level, the yogurt was firmer and showed greater chewiness, which is highly desirable for Greek yogurt. Therefore, the results suggested that lyophilized purple-fleshed sweet potato powder is a potential multifunctional natural ingredient.